Analisis Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) sebagai upaya Penanggulangan Kemiskinan di Kota Langsa - Puti Andiny; Nurjannah Nurjannah (Universitas Serambi Mekkah, 2018)
This study aims to analyze the empowerment of Micro Small and Medium Enterprises to overcome urban poverty in Langsa. The data used are primary data, was collected through observations, interviews, and questionnaires. The population in this research is Small and Medium Micro Enterprises in Langsa City as many as 185 business actors. Samples were taken as many as 30 percents of the total population, as many as 60 business actors. This research uses a descriptive method. The technique of collecting data using a purposive random sampling method. The results showed that the process of empowering SMEs able to cope with poverty, increase economic growth and contribute to absorbing labor.This study aims to analyze the empowerment of Micro Small and Medium Enterprises to overcome urban poverty in Langsa. The data used are primary data, was collected through observations, interviews and questionnaires. The population in this research is Small and Medium Micro Enterprises in Langsa City as many as 185 business actors. Samples were taken as many as 30 percent of the total population, as many as 60 business actors. This research uses a descriptive method. Technique of collecting data using purporsive random sampling method. The results showed that the process of empowering SMEs able to cope poverty, increase economic growth and contribute to absorbing labor.